2023
DOI: 10.3991/ijim.v17i08.39215
|View full text |Cite
|
Sign up to set email alerts
|

The Use of English Language Learning Videos Designed Through Canva App: Students’ Perceptions

Abstract: Recordings are exceptionally good at passing on the teacher's eagerness and objectives for teaching English, which are difficult to clarify. It can be passed on within the video. The teacher used to get the learning videos from YouTube or Facebook. Utilizing these learning videos makes lessons more curious within the classroom. Communication and innovation can be used as curious and fun media. Remembering that in the current circumstance, learning can be worn out both online and offline, at that point, the tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Portable technologies like smartphones and tablets show the potential to improve ELT, especially in areas with limited access to the target language (Abugohar et al, 2019). Ilyas et al (2023) found Canva beneficial for English curriculum understanding, while Indriani and Widiastuti (2021) reported positive student perceptions of Moddle for learning management. Sari and Wahyudin (2019) emphasized Instagram's value in connecting with native speakers.…”
Section: The Integration Of Web-based and Non-web-based Ict In Eltmentioning
confidence: 99%
“…Portable technologies like smartphones and tablets show the potential to improve ELT, especially in areas with limited access to the target language (Abugohar et al, 2019). Ilyas et al (2023) found Canva beneficial for English curriculum understanding, while Indriani and Widiastuti (2021) reported positive student perceptions of Moddle for learning management. Sari and Wahyudin (2019) emphasized Instagram's value in connecting with native speakers.…”
Section: The Integration Of Web-based and Non-web-based Ict In Eltmentioning
confidence: 99%
“…The available features can be developed as creatively as possible to make classroom learning more interactive and communicative, thus more enjoyable and easier to understand (Tri Wulandari & Adam Mudinillah, 2022). The advantages of Canva include increasing teachers' creativity in designing learning media, offering various graphic designs, templates, and animations, and being accessible via smartphone or laptop (Ilyas et al, 2023;Tanjung & Faiza, 2019). The use of technology for learning media like Canva-based Digital Flipbooks can attract students' interest and motivation to learn (Hidayah et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In the modern society of globalization and digitization, the cultivation of English listening and speaking ability is becoming increasingly important. This cross-cultural communication ability has become one of the most important universal skills in the 21st century [1][2][3]. English listening and speaking ability plays an irreplaceable role, from academic research and business communication to communication in daily life.…”
Section: Introductionmentioning
confidence: 99%